Intravitreal administration of endothelin type A receptor or endothelin type B receptor antagonists attenuates hypertensive and diabetic retinopathy in rats. (November 2018) - Alrashdi, Saeed F.; Deliyanti, Devy; Wilkinson-Berka, Jennifer L.
Abstract: Hypertension is an independent risk factor for diabetic retinopathy, yet anti-hypertensive medications such as blockade of angiotensin II do not completely protect against vision-threatening vascular disease. We hypothesized that the potent vasoactive factor, endothelin (ET), is up-regulated in diabetic retinopathy and antagonism of the ET type A receptor (ETRA) or ET type B receptor (ETRB) ameliorates retinal vascular leakage independently of any blood pressure lowering effects. Spontaneously hypertensive rats (SHR) and their normotensive and genetic controls, Wistar Kyoto rats, were randomized to become diabetic or non-diabetic and studied for 8 weeks. Rats were further randomized to receive by intravitreal injection the ETRA antagonist, BQ123, the ETRB antagonist, BQ788, or vehicle, 5 days after the induction of streptozotocin diabetes and 4 weeks later. The treatments had no effect on systolic blood pressure which remained elevated in SHR. ET-1, ET-2, ETRA and ETRB were expressed in retina and retinal pigment epithelium (RPE)/choroid and increased by hypertension or diabetes. BQ123 reduced ET-1 and ET-2 expression in retina and RPE/choroid, while BQ788 had a similar effect but did not influence the mRNA levels of ET-1 in retina. Retinal vascular leakage and Müller cell stress as well as vascular endothelial growth factor (VEGF) expression in retina and RPE/choroid, were increased by hypertension or diabetes and there was an additive effect of these conditions. Treatment with BQ123 or BQ788 effectively reduced these events as well as the elevated levels of inflammatory factors in the retina. Our findings indicate that local ET systems exist in the retina and RPE/choroid that are up-regulated by hypertension and diabetes. The ability of locally delivered ET receptor antagonists to supress these overactive ET systems and reduce retinal vascular leakage and VEGF in the presence of hypertension indicate the potential of these approaches for the treatment of diabetic retinopathy. Highlights: Hypertension and diabetes increase endothelin 1 and 2 in retina and RPE/choroid. Intravitreal endothelin (ET) receptor A or B blockade reduce vascular leakage. Intravitreal ET receptor A or B blockade reduce VEGF in retina and RPE/choroid. Intravitreal ET receptor A or B blockade reduce retinal gliosis and inflammation. ET receptor A or B blockade confers ocular protection in diabetes and hypertension.